THE EFFECT OF CADMIUM CHLORIDE TO THE STERILITY OF MALE RAT - Syarifuddin Tato; Puspa Wikan Sari (Jurnal Sain Veteriner, 1996)
The effect of cadmium chloride (CdO2) to the sterility of male rat have been observed to the first generation (Fj).Sixty white rats consisted of 30 male rats at 3 weeks old divided Into 6 groups and were given CdCl2 orally ad libitum for 42 days, Tl»e concentration of CdCl2 for each group was 0 ppin (group I), 200 ppm (group H), 100 ppm (group ID), 50 ppm (group IV), 25 ppm (group V) and 12,5 ppm (group VI). After treatments, aii male rats were mated with female rats by mixing a couple of rats in a cage for 7 days. Then male rats were kiiied all to examine the histopathoiogy of their testis. The female rats were kept until 18 days of pregnancy, then all were killed. The percentage of pregnancy and the number of baby in each female rat were counted. The histopamoiogy of seminiferous tubules of testis were analysed qualitatively.The results showed that CdCl2 at 12,5 and 25 ppm caused 20% and 40% of infertility. 50 ppm of CdCfe caused 100% of infertility and necrosis of spermatocyte and spermaride celk; there no spematozoa in the seminiferous tubules.